Homo/transexualidades e família: uma análise a partir do 1º "Grupo de pais de homossexuais" do município de Sorocaba - Nascimento, Rogéria Fernandes do (Universidade Federal de São Carlos, 2015)
The research is linked with the Education StrictuSensu Post-Graduation Program of UFSCar – Sorocaba and started with the participation in a group of homosexual/transgenderparents that used to arrange meetings of mutual help to fight against homophobia in the family context, the GPH, that has been established as a public policy in Sorocaba-SP since April/2013. The investigation was takento find out the limits and possibilities of this homophobia combat space through the presentation and analysis of categories and social conventions that merge there. From the theoretical field of gender and post-structuralistsexuality, it was sought to investigate the relations between families and homosexual/transgender, particularly the lives of the parents with the objective of comprehending and integrating their children. Because learning and investigating this relationship space is a process that cannot be measured to quantifiable variables, this research is qualitative. The methodological work was accomplished through the bibliographical research of documents and field studies, using the following procedures: documental analysis, interviews, prioritizing the participating observation and speech quantitative analysis in the perspective of events that took place in the maternity. The most difficult elements of this journey is the binary speech inheritance – man/woman, male/female, straight/homo – produced and reproduced daily inside the homophobic speech as in those that in some way are favorable to gender diversity and sexual orientation. The difficulties felt and supposedly faced by the GPH parents and the categories and social conventions mobilized in this journey were considered to be linked to differences built – social and culturally – translated in power relationships that rank gender, rendering inferior all forms that do not correspond to the linearity of sex, gender, desire and sexual practice. The implementation and participation at the GPH Sorocaba shown, not only the strength of heteronormativity, but also that the different fugitive form of being and living the genders and sexualities, generally not accepted but tolerated, highlighting that there is no social convention detachment in this context. At the same time, the attribution of new senses, the questioning of built “truths” that, for a long time, were naturalized and reproduced by these LGBT parents shows that public policies aimed to homophobic confrontation in family context have an important role to mitigate it.
Homosexual/transgenderand family: An analysis from the 1st "group ofhomosexual parents" at Sorocaba city
Keywords: Homossexualidade; Homosexuality; Família; Families; Ajuda mútua; Mutual Help; Homo/transexualidades; Homosexual/transgender; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS